Should Internet Researchers Use Ill-Gotten Information? - Douglas, David M. (Science & Engineering Ethics, 2018)
This paper describes how the ethical problems raised by scientific data obtained through harmful and immoral conduct (which, following Stan Godlovitch, is called ill-gotten information) may also emerge in cases where data is collected from the Internet. It describes the major arguments for and against using ill-gotten information in research, and shows how they may be applied to research that either collects information about the Internet itself or which uses data from questionable or unknown sources on the Internet. Three examples (the Internet Census 2012, the PharmaLeaks study, and research into keylogger dropzones) demonstrate how researchers address the ethical issues raised by the sources of data that they use and how the existing arguments concerning the use of ill-gotten information apply to Internet research. The problems faced by researchers who collect or use data from the Internet are shown to be the same problems faced by researchers in other fields who may obtain or use ill-gotten information.